Pengaruh bauran pemasaran terhadap keputusan penggunaan jasa pada Hotel Furaya - Muhammad Jamil Hazfa; Aida Nursanti; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at Hotel Furaya Pekanbaru. Which aims to determine the effect of the marketing mix decisions on the use of services Furaya pekanbaru hotel. Respondents who are consumers staying at hotels Furaya Pekanbaru, as many as 100 people using accidental sampling technique. In analyzing the data, the writer uses descriptive analysis that compares the data with various theories that support and explain or describe nature and use SPSS (Statistical Package for Social Science) version 17.00. To see the life style of the marketing mix analysis, the authors use multiple regression formula (multiple regression). It is shown that the variable (X1) products, is greater than t-table means there is a significant influence on consumer decisions. variable (X2) price, less than the t-table means that there is a significant influence on consumer decisions. variable (X3) promotion, greater than t-table means there is a significant influence on consumer decisions. variable (X4) people, is greater than t-table means there is a significant influence on consumer decisions. variable (X5) process, is greater than t-table means there is a significant influence on consumer decisions. variable (X6) customer service is greater than t-table means there is a significant influence on consumer decisions. Based on the research coefficient of multiple determination (R2) 0.3716 magnitude. It shows that the two independent variables, namely the quality of service together have the effect of 37.16% of the consumer decision while the remaining 62.84% are influenced by other variables not examined.Keywords: Marketing Mix, DecisionUse of Services